Thyroid Peroxidase Antibody and Screening for Postpartum Thyroid Dysfunction - Adlan, Mohamed A. (SAGE-Hindawi Access to Research, 2011)
Postpartum thyroid dysfunction (PPTD) is a common disorder which causes considerable morbidity in affected women. The availability of effective treatment for hypothyroid PPTD, the occurrence of the disease in subsequent pregnancies and the need to identify subjects who develop long term hypothyroidism, has prompted discussion about screening for this disorder. There is currently no consensus about screening as investigations hitherto have been variable in their design, definitions and assay frequency and methodology. There is also a lack of consensus about a suitable screening tool although thyroid peroxidase antibody (TPOAb) is a leading contender. We present data about the use of TPOAb in early pregnancy and its value as a screening tool. Although its positive predictive value is moderate, its sensitivity and specificity when used in early pregnancy are comparable or better compared to other times during pregnancy and the postpartum period. Recent studies have also confirmed this strategy to be cost effective and to compare favourably with other screening strategies. We also explore the advantages of universal screening.